2020
DOI: 10.1112/blms.12397
|View full text |Cite
|
Sign up to set email alerts
|

A note on band surgery and the signature of a knot

Abstract: Band surgery is an operation relating pairs of knots or links in the three-sphere. We prove that if two quasi-alternating knots K and K of the same square-free determinant are related by a band surgery, then the absolute value of the difference in their signatures is either 0 or 8. This obstruction follows from a more general theorem about the difference in the Heegaard Floer dinvariants for pairs of L-spaces that are related by distance one Dehn fillings and satisfy a certain condition in first homology. Thes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
(87 reference statements)
0
8
0
Order By: Relevance
“…Moore and Vazquez [15,Corollary 3.7] show that a distance one surgery along any knot in L(n, 1) yielding L(−n, 1) with n > 1 square-free and odd exists if and only if n = 5. In fact, in the proof of [15,Corollary 3.7], the assumption that n is square-free is just used to show that any knot admitting this type of surgery must be null-homologous.…”
Section: Thus the Hat Versionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moore and Vazquez [15,Corollary 3.7] show that a distance one surgery along any knot in L(n, 1) yielding L(−n, 1) with n > 1 square-free and odd exists if and only if n = 5. In fact, in the proof of [15,Corollary 3.7], the assumption that n is square-free is just used to show that any knot admitting this type of surgery must be null-homologous.…”
Section: Thus the Hat Versionmentioning
confidence: 99%
“…Apart from L(n, 1) (respectively T (2, n)) is the simplest lens space (respectively 2-bridge link) type, it is also motivated from DNA topology. In biology, circular DNA (f) Band surgery from T (2, 5) to T (2, −5) constructed by Zeković (see [27] and [15]). can be modeled as a knot or link, and torus knots or links T (2, n) are a family of DNA knots or links occurring frequently in biological experiments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, knot theory has many applications in biology, particularly in DNA topology (Adams, 1994). In Moore and Vazquez (2020), coherent band surgery, conversion of a knot into a two-component link, and noncoherent band surgery, which is similar to coherent band surgery except the orientations are not retained, is used in the study of low-dimensional topology, particularly in DNA topology.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 illustrates such a smoothing. In the reverse direction, Moore and Vazquez [23] showed that T (2, 5) is unique among positive torus knots T (2, m), with m square-free, for which such a move exists. The paper [24] reports on extensive computer searches that have discovered chiral smoothings for the knots 8 8 and 8 20 .…”
Section: Introductionmentioning
confidence: 99%